PENGEMBANGAN MODUL P5 CEGAH ANEMIA DENGAN PANGAN SEHAT SEBAGAI UPAYA DUKUNG CEGAH STUNTING DI SMA NEGERI 1 SUWAWA - Hulalata, Wiranda; Nusantari, Elya; Solang, Margaretha; S. Kumaji, Syam; Fajriyani Usman, Nurul (Jurnal Biogenerasi, 2025)
This study aims to develop a module for the Pancasila Student Profile Strengthening Project (P5) with the theme "Prevent Anemia with Healthy Food as an Effort to Support Stunting Prevention" and test its practicality as a teaching tool in project-based learning. This study was conducted at SMA Negeri 1 Suwawa using the Research and Development (R&D) method with the ADDIE approach, which focused on the analysis, design, and development stages. The module was developed to support students' understanding of the relationship between anemia, nutrition, and stunting, as well as to raise awareness of the importance of healthy food consumption. The practicality of the module was tested through a limited trial involving one biology teacher and 30 grade XI students. Data were obtained through questionnaires, observations of learning implementation, and assessments by material and construct experts. The results showed that the P5 module developed had a very high level of practicality. Teacher responses showed an average score of 94%, with a perfect assessment in terms of usability and suitability for students. The students’ responses were also very positive, with an average of 87% covering the aspects of interest, ease of use, and benefits. Observations of the implementation of learning showed an average implementation of 100% in preliminary activities, 92–94% in core activities, and 96% in closing activities. Thus, the module is declared feasible and practical to use in the learning process to support the strengthening of students’ character and knowledge through a health-themed project approach.